American presidents, deportations, and human rights violations : from Carter to Trump / Bill Ong Hing, University of San Francisco. - Hing, Bill Ong (Cambridge University Press, 2019)
Of the many issues polarizing societies today, immigration is one of the most contentious. In the United States, as in Europe, immigration was a defining issue in recent national elections. Immigration not only involves government policies but also the human rights of millions of people. American Presidents, Deportations, and Human Rights Violations studies how recent immigration policies in the United States developed during the Obama administration and are now being expanded in the first months of the Trump presidency. Documenting the harsh treatment of immigrants over the past twenty years, Bill Ong Hing shows how mass detention and deportation of immigrants, from Clinton's two terms and the Bush administration, have escalated even higher. This book questions what price the United States is willing to pay for such harsh immigration policies in terms of our national values, and the impact on the lives of the millions of immigrants who deserve the full protection of universal human rights obligations.